(untitled) (Journal of the College of Basic Education, 2022)
Each scientific research has objectives that it seeks to achieve. The objectives of the current research lie in the following:- Emphasizing the importance of the expectations guide strategy as a strategy that has not been touched upon before.Emphasizing the importance of reading comprehension as the main objective of the reading process.Emphasis on following active learning as directed to the learner’s activity.- Emphasis on creating a lively educational atmosphere by following effective strategies in the field of reading